Contrasting effect of prepulse signals on performance of Toxoplasma-infected and Toxoplasma-free subjects in an acoustic reaction times test - Příplatová, Lenka; Sebánková, Blanka; Flegr, Jaroslav (PLoS One, 2014)
BACKGROUND: About 30% of people on Earth have latent toxoplasmosis. Infected subjects do not express any clinical symptoms, however, they carry dormant stages of parasite Toxoplasma for the rest of their life. This form of toxoplasmosis is mostly considered harmless, however, recent studies showed its specific effects on physiology, behaviour and its associations with various diseases, including psychiatric disorders such as schizophrenia. Individuals who suffer from schizophrenia have about 2.7 times higher prevalence of Toxoplasma-seropositivity than controls, which suggests that some traits characteristic of schizophrenic patients, including the sex difference in schizophrenia onset, decrease of grey matter density in specific brain areas and modification of prepulse inhibition of startle reaction could in fact be caused by toxoplasmosis for those patients who are Toxoplasma-seropositive. METHODOLOGY/PRINCIPAL FINDINGS: We measured the effect of prepulse inhibition/facilitation of the startle reaction on reaction times. The students, 170 women and 66 men, were asked to react as quickly as possible to a startling acoustic signal by pressing a computer mouse button. Some of the startling signals were without the prepulse, some were 20 msec. preceded by a short (20 msec.) prepulse signal of lower intensity. Toxoplasma-seropositive subjects had longer reaction times than the controls. Acoustic prepulse shorted the reaction times in all subjects. This effect of prepulse on reaction times was stronger in male subjects and increased with the duration of infection, suggesting that it represented a cumulative effect of latent toxoplasmosis, rather than a fading out after effect of past acute toxoplasmosis. CONCLUSIONS: Different sensitivity of Toxoplasma-seropositive and Toxoplasma-seronegative subjects on effect of prepulses on reaction times (the toxoplasmosis-prepulse interaction) suggested, but of course did not prove, that the alternations of prepulse inhibition of startle reaction observed in schizophrenia patients probably joined the list of schizophrenia symptoms that are in fact caused by latent toxoplasmosis.
Keywords: úleková reakce; dospělí; Female; Toxoplasmosis; reakční čas; Adult; mladý dospělý; ženské pohlaví; Schizophrenic Psychology; lidé; Toxoplasma; schizofrenie; Sex Factors; Male; sexuální faktory; Young Adult; Schizophrenia; Reaction Time; toxoplazmóza; Reflex, Startle; mužské pohlaví; schizofrenie (psychologie); Humans